2023
DOI: 10.1002/adfm.202301174
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Fiber for Synchronous Bio‐Sensing and Power Supply in Sweat Environment

Abstract: Continuous monitoring of human sweat, which enables highly sensitive multiple biomarkers analysis with a portable power supply, is increasingly desired for the remote healthcare industry. Smart fibers with on‐demand functionality are ideal candidates for fabricating noninvasive and conformal bioelectronic devices owing to their considerable flexibility. Herein, a multifunctional textile patch based on a reduced graphene oxide (rGO)/tetra‐aniline (TANi) fiber for simultaneous biomarker monitoring and energy sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Sweat samples obtained quickly over a short period of time are representative of human physiology, so the fast response of the sensor ensures the reliability of the data in the face of varying perspiration rates . Compared to previously reported sweat sensors, TPFV/CPP yarn demonstrated superior sensitivity and fast response (Figure i).…”
Section: Results and Discussionmentioning
confidence: 96%
“…Sweat samples obtained quickly over a short period of time are representative of human physiology, so the fast response of the sensor ensures the reliability of the data in the face of varying perspiration rates . Compared to previously reported sweat sensors, TPFV/CPP yarn demonstrated superior sensitivity and fast response (Figure i).…”
Section: Results and Discussionmentioning
confidence: 96%
“…363 This would enable reliable, long-term tracking of gestures indicating various directions. 364,365 Here, Xu et al 366 described the creation of a kind of flexible, multifunctional hydrogel fiber that displays spider silk's reversible adhesiveness on a variety of surfaces. This fiber also exhibits conductivity and can withstand freezing temperatures below approximately 40 • C. Additional strain-resistance testing revealed that within 200 stretch release cycles, with minimal drifting, the hydrogel fibers could identify strains between 0.5% and 34.5%.…”
Section: 9mentioning
confidence: 99%
“…The use of electrochemical sensors to monitor biomarkers in human sweat is a common method [84][85][86]. For instance, a multifunctional textile sensor made of rGO/polyaniline (PANI) hybrid fibers can be used to monitor multiple biomarkers simultaneously [87]. Taking advantage of the excellent charge storage capacity of polyaniline in bioelectrolyte solution, the authors assembled two fiber electrodes into a fiber-based supercapacitor with an obvious linear relationship with pH change.…”
Section: Fiber-based Biofluid Signal Sensorsmentioning
confidence: 99%